Rainbow beach - Manning, Bella A (Department of English Language and Literature, 2015)
Rainbow Beach is the story of a family that escapes to a faraway place to forget the past and the past that follows them there. It is the story of a landscape, at times serene, at times explosive, that mirrors them and that they come to adore and yet resist. And it is the story of a father struggling under the weight of his memories and the daughter who loves him fiercely and senses the coming collapse and whose own memories take root in a part of the soul too deep to be erased.